Effect Of Waste Gypsum From Ceramic Slip Casting Mould On The Properties Of Portland Cement. - Chandara, Chea (2017)
The aim of this work is to investigate the possibility of using waste gypsum (CaSO4 .2H2O) which is the waste material from the hydration of plaster of Paris in ceramic factory as a replacement or alternative material to natural gypsum (CaSO4.2H2O) in cement production. Prior to cement grinding test work, the raw materials such as clinker, natural gypsum and waste gypsum had been characterized using X-Ray Diffraction, X-Ray Fluorescence, Differential Scanning Calorimetry I Thermogravimetry and Field Emission Scanning Electron Microscopy.